2007
DOI: 10.1186/1477-5751-6-7
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and oestrogen receptor polymorphisms in developmental dysplasia of the hip and primary protrusio acetabuli – A preliminary study

Abstract: We investigated the association of developmental dysplasia of the hip (DDH) and primary protrusion acetabuli (PPA) with Vitamin D receptor polymorphisms Taq I and Fok I and oestrogen receptor polymorphisms Pvu II and Xba I. 45 patients with DDH and 20 patients with PPA were included in the study. Healthy controls (n = 101) aged 18–60 years were recruited from the same geographical area. The control subjects had a normal acetabular morphology based on a recent pelvic radiograph performed for an unrelated cause.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…Increased body weight increases the stress across the developing hip joint leading to subluxation [17, 42, 43]. Vitamin D plays a role in DDH, as humans with homozygosity for the mutant Taq1 vitamin D receptor t allele demonstrate increased acetabular dysplasia [44]. Vitamin D levels may vary by season due to seasonal variation in vitamin D dietary content in both humans and animals [4552].…”
Section: Discussionmentioning
confidence: 99%
“…Increased body weight increases the stress across the developing hip joint leading to subluxation [17, 42, 43]. Vitamin D plays a role in DDH, as humans with homozygosity for the mutant Taq1 vitamin D receptor t allele demonstrate increased acetabular dysplasia [44]. Vitamin D levels may vary by season due to seasonal variation in vitamin D dietary content in both humans and animals [4552].…”
Section: Discussionmentioning
confidence: 99%
“…However, one possible risk factor in the Sámi population for developmental dysplasia of the hip (DDH) was the earlier tradition of wrapping up the child and laying it in the Sámi/ Lapp cradle with the hips extended and adducted. Also, the Sámi population examined in this study live north of the Arctic circle, where the sun totally disappears for some months yearly, and a possible link between vitamin D and DDH can be suspected [11].…”
Section: Discussionmentioning
confidence: 99%
“…A genetic aetiology has been proposed in those with AD [15]. Hereditary factors, particularly sex hormones such as oestrogen, may be strongly associated with congenital dislocation of the hip and AD [19]. Kapoor et al reported that ER gene polymorphism XbaI gene polymorphism was more common in AD than in controls.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic variation in hormone-related genes may represent a possible determinant of the risk or severity, especially when considering the possible effect of joint laxity on AD [2]. In Caucasians, oestrogen receptor (ER) and vitamin D receptor (VDR) gene polymorphism may be associated with AD, although no statistical significance has been observed [19]. An rotational acetabular osteotomy (RAO) is frequently performed to treat patients with symptomatic AD who show less than 20°of centre-edge (CE) angle to forestall the expected progress of degenerative change of the hip joint [25][26][27].…”
Section: Introductionmentioning
confidence: 99%